Writing Assessment Methods Utilized by Senior High School English Teacher in Jember: A CASE STUDY - Megawati, Enny; Ariyanto, Sugeng; Suharjito, Bambang (EFL Education Journal, 2022)
This research was aimed at writing assessment methods utilized by senior high school English teacher in Jember. This research applied qualitative method with grade eleven of English teacher as the research participants. The data were analyzed using thematic analysis to know the assessment methods employed by the senior high school English teacher. The result of this research shows that the teacher used process assessment and product assessment to assess students’ writing.